Role of N-terminal domains of p400 ATPase in the ATM interaction and DNA damage response : a thesis presented in partial fulfillment of the requirements for a the degree of Master of Science (MSc) in Genetics at Massey University, Manawatū, New Zealand - Weber, Lauren Elizabeth (Massey University, 2016)
Efficient repair of damaged DNA and preservation of genomic integrity is integral in the maintenance of proper cellular function and prevention of unrestricted cell proliferation. One critical threat to the stability of the genome is the double strand break (DSB), arguably one of the most cytotoxic lesions to DNA. Interference with the DSB repair mechanism can lead to dysregulation of cellular systems and the prospective development of malignancies. Two critical proteins in DBS repair are the Ataxia Telangiectasia Mutated (ATM) kinase, a serine/threonine kinase from the Phosphatidylinositol 3-Kinase-related Kinase (PIKK) family, and p400, an ATPase chromatin remodeler. ATM is one of the first responders to DSBs and is responsible for the phosphorylation of a multitude of protein substrates including the histone variant H2AX. Beyond its phosphorylation ability, ATM has been proposed as a potential shuttle for other repair machinery, aiding in the early and efficient recruitment of proteins to the DNA damage foci. One such proposed protein is p400. The exact role of p400 in DSB repair is unknown but previous studies show that there is a decrease in repair efficiency in its absence. A prospective interaction is supported by previous studies in which p400 and p400 N-terminal derivatives co-immunoprecipitate with ATM in vivo in HEK293T cells. This study aimed to confirm the interaction of ATM and p400 N-terminal derivatives in vitro and explore the functional implications of the association in vivo in U2OS cells. It was not possible to isolate full-length p400 derivatives in vitro and thus no conclusive results were obtained. Functional assays revealed the ability of one p400 fragment, F1, to inhibit DNA repair and cell proliferation after DNA double-strand break induction with bleomycin. Ectopic expression of the other two p400 N-terminal fragments, F2 and F3, induced an inhibition of cell proliferation under standard growth conditions. Although no conclusive results were acquired, a trend emerged suggesting that N-terminal fragment F1 is able to interfere with ATM protein-protein interactions resulting in a decrease in the efficiency of the DNA damage response and repair. These results implicate F1 as a potential target for further research in both DNA repair and cancer therapy.
Keywords: DNA repair; Cancer cells; Growth; Regulation; Protein kinases; Inhibitors; Therapeutic use; Chromatin; Structure; Cancer; Gene therapy; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics